Pembocoran Rahasia Dagang Perusahaan oleh Mantan Karyawan : Perlindungan Hukum dan Klausula Rahasia Dagang - Adri Sadewa Sirait; Berkat Perjuangan Ndruru; Roy Nanda Kesuma; Bambang Fitrianto (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
Trade secrets are an important part of Intellectual Property Rights (IPR) that play a strategic role in maintaining a company's competitive advantage. Protecting information that is not generally known, has economic value, and is kept confidential is very important, especially in the midst of globalization and technological advances that increase the risk of information leakage. Law No. 30 of 2000 concerning Trade Secrets is the main legal basis in Indonesia, in line with international agreements such as WTO/TRIPS. This research uses normative juridical methods to analyze trade secret legal protection, including based on property rights theory, contract theory, and tort theory. In addition, the role of employment contract clauses that regulate obligations to maintain confidentiality and prohibitions on working for competing companies after termination are discussed as preventive strategies. This research confirms the importance of awareness and concrete legal steps from business owners to protect their trade secrets effectively.